Morphological and anatomical studies of the seeds and seedlings of Eucalyptus pilularis and E. umbra - Beltrati, C. M. (Revista de Biologia Tropical, 1981)
Morphological and anatomical aspects of seeds and seedlings of Eucalyptus pilularis Sm. and E. umbra R.T. Baker were studied in detail and fovnd to be similar, wlth the exception of sorne anatomical features of the testa and the average length of the fertile seeds, which is significantly different for the two species.

Se estudiaron en detalle aspectos morfológicos y anatómicos de semillas y plántulas jóvenes de Eucalyptus pilularis Sm. y E. umbra R.T. Baker. Se encontró que eran similares a excepción de algunos aspectos anatómicos de la testa y del promedio de longitud de las semillas fértiles, que es significativamente diferente en estas dos especies.